Adoption of building information modeling in developing countries: a phenomenological perspective - Sahil, Abdul Qadeer, author; Glick, Scott, advisor; Valdes-Vasquez, Rodolfo, advisor; Folkestad, James, committee member (Colorado State University. Libraries, 2016)
Building Information Modeling (BIM) is a cutting edge technology that has addressed prominent challenges in the Architecture, Engineering and Construction (AEC) industries in most of the developed countries. Construction industries in developing countries due to identified challenges and unavailability of the clear understanding of best practices, are dithering whether to adopt this technology. The scope of this study was how to facilitate BIM adoption in developing countries. A phenomenological design approach was considered to seek early adopters’ and BIM professionals’ lived experiences on similar situations and how did they triumph over the hindrances against BIM adoption and made its implementation successful. A total of six participants with extensive BIM experience and first hand BIM application knowledge were interviewed. The result confirms BIM adoption issues similarities in both developed and developing countries. Recommended best practices for new BIM users in four categories of education requirement, infrastructure requirement, sound practices, and working with partners with no previous BIM experience is represented in chapter five. The study limitation was the inability to reach out BIM professionals in developing countries therefore, considering the similarities of BIM adoption issues, five of the participants selected for this study were from the United States whereas one participant was selected from developing countries. The study concludes with recommendation for further study in this field.
Keywords: construction; technology; engineering; architectural